Mekhanizmy resheniya operativno-takticheskikh zadach v igrovykh vidakh sporta - Rodionov, A. V.; Topyshev, O. P.; Usakov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
Review about mechanisms of operative-tactic problems' solving in sports games today.